An assessment of factors contributing to treatment adherence and knowledge of TB transmission among patients on TB treatment - Siziya Seter; Tuba Mary; Kaona Frederick AD; Sikaona Lenganji (BMC, 2004)
Abstract Background The treatment guidelines for tuberculosis treatment under Directly Observed Treatment, Short-course (DOTS) have been a common strategy for TB treatment in Zambia. The study was carried out in Ndola, Zambia, to investigate factors contributing to treatment non-adherence and knowledge of TB transmission among patients on TB treatment, in order to design a community-based intervention, that would promote compliance. Methods A household-based survey was conducted in six randomly selected catchment areas of Ndola, where 400 out of 736 patients receiving TB treatment within the six months period, were recruited through the District's Health Management Board (DHMB) clinics. All patients were interviewed using a pre-tested structured questionnaire, consisting of i. Socio-demographic characteristics ii. Socio-economic factors iii. Knowledge about TB transmission and prevention iv. Patterns in health seeking behaviour and v. TB treatment practices at household level. Results Most male TB patient respondents tended to be older and more educated than the female TB patient respondents. Overall, 29.8% of the patients stopped taking their medication. There were 39.1% of the females and 33.9% of the males, who reported that TB patients stopped taking their medication within the first 2 months of commencing treatment. Age, marital status and educational levels were not significantly associated with compliance. The major factors leading to non-compliance included patients beginning to feel better (45.1% and 38.6%), lack of knowledge on the benefits of completing a course (25.7%), running out of drugs at home (25.4%) and TB drugs too strong (20.1% and 20.2%). There was a significant difference [OR = 1.66, 95% CI 1.23, 2.26] in TB knowledge, with more males than females reporting sharing of cups as a means for TB transmission, after adjusting for age, marital status and educational levels. Significantly [p = 0.016] more patients who had resided in the study for less than two years (59%) were more likely to report mother to child transmission of TB, compared to 41.2% of those who had been in the area for more than 2 years. Conclusion This study established that 29.8% of TB patients failed to comply with TB drug taking regimen once they started feeling better.